Transdisciplinaries strategies and the “medical act” in the health undergraduation students’ comprehension. Exploratory study - Machado, William César Alves; Portes, Danielle Braga; Berbert, Felipe Azevedo; Santana, Camila Reis de; Mattos Junior, Luiz dos Santos Freitas; Mello, Patricia do Carmo (Online Brazilian Journal of Nursing, 2007)
It is a descriptive and exploratory research, with qualitative approach, gone back to analyze the repercussions of the “Medical Act” (MA) starting from the health sciences undergraduation students' point of view and to stimulate the development of the critical sense concerning the transdisciplinarity for harmony of the work in team. The subject of the study are 105 undergraduation students, 34 of Nursing (6th Semester), 45 of Nutrition (2nd Semester), 17 of Physiotherapy (1st Semester) and 9 of Medicine (4th Semester), and the instrument used for collection of data limited to one open subject, seeking to capture the meanings of the medical act for the same ones. The data collection happened in the first and second semesters of 2004. The results aim MA as setback for the transdisciplinarity, due to the improper appropriation of the knowledge in health for the medicine, opposing the effective legislation. It is ended that the incentive to the discussions on the theme with students of the area of health facilitates larger elucidate of each category concerning the domain of knowledge of the others, specially, in the understanding that AM infringes one of the most important beginnings of the transdisciplinarty, the work in team.